A comparative analysis of microscopic alterations in modern and ancient undecalcified and decalcified dry bones. Issue 2 (27th October 2017) - Caruso, Valentina; Cummaudo, Marco; Maderna, Emanuela; Cappella, Annalisa; Caudullo, Giorgio; Scarpulla, Valentina; Cattaneo, Cristina
Abstract: Objectives: The present study aims to evaluate the preservation of the microstructure of skeletal remains collected from four different known burial sites (archaeological and contemporary). Histological analysis on undecalcified and decalcified thin sections was performed in order to assess which of the two techniques is more affected by taphonomic insults. Materials and Methods: A histological analysis was performed on both undecalcified and decalcified thin sections of 40 long bones and the degree of diagenetic change was evaluated using transmitted and polarized light microscopy according to the Oxford Histological Index (OHI). In order to test the optical behavior of bone tissue, thin sections were observed by polarized light microscopy and the intensity of birefringence was evaluated. Results: The more ancient samples are generally characterized by a low OHI (0–1) with extensive microscopic focal destruction; recent samples exhibited a better preservation of bone micromorphology. When comparing undecalcified to decalcified thin sections, the latter showed an amelioration in the conservation of microscopic structure. As regards the birefringence, it was very low in all the undecalcified thin sections, whereas decalcification process seems to improve its visibility. Discussion: The preservation of the bone microscopic structure appears to be influenced not only by age, but also by the burial context. Undecalcified bones appear to be more affected by taphonomical alterations, probably because of the thickness of the thin sections; on the contrary, decalcified thin sections proved to be able to tackle this issue allowing a better reading of the bone tissue.